Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.energy.2018.12.196
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of organic Rankine cycle integrated with double latent thermal energy storage for engine waste heat recovery

Abstract: In this work, organic Rankine cycle (ORC) integrated with Latent Thermal Energy Storage (LTES) system for engine waste heat recovery has been proposed and investigated to potentially overcome the intermittent and fluctuating operational conditions for vehicle applications. A melting-solidification model has been established to investigate and compare the performance of twelve Phase Change Materials (PCMs) under different heat source conditions. Among the twelve PCMs, LiNO3-KCl-NaNO3 is identified as the optima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Cases 2 and 3 also shows that LiNO3-KCl-NaNO3 is the optimal PCM for this temperature range. Whilst other PCM options show a slight increase in total work output for the system, the LiNO3-KCl-NaNO3 has by far the largest discharge time, meaning the ORC can maintain a stable temperature profile for a total of 48.8 minutes whilst also generating a large amount of power output [8].…”
Section: Double Latent Thermal Energy Storage Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cases 2 and 3 also shows that LiNO3-KCl-NaNO3 is the optimal PCM for this temperature range. Whilst other PCM options show a slight increase in total work output for the system, the LiNO3-KCl-NaNO3 has by far the largest discharge time, meaning the ORC can maintain a stable temperature profile for a total of 48.8 minutes whilst also generating a large amount of power output [8].…”
Section: Double Latent Thermal Energy Storage Integrationmentioning
confidence: 99%
“…Yu et al investigated the integration of double Latent Thermal Energy Storage (LTES) into a standard ORC setup [8]. In this study, the authors evaluate the effectiveness of different Phase Changing Materials (PCMs) utilised in such configurations in order to overcome the unsteady nature of exhaust gases of which an ORC must work upon.…”
Section: Orc With Integrated Double Latent Thermal Energy Storagementioning
confidence: 99%
“…The research on ORC is not limited to only the configuration itself but also includes the energy storage system. For instance [43], managed to integrate a double latent thermal energy storage into the ORC system for engine WHR. Moreover, the planned solution was also able to reduce the fluctuation of the engine exhaust heat.…”
Section: Rankine Cyclementioning
confidence: 99%
“…In this study, the PCM was simplified as big heat capacity and the results indicated that the PCM-based system could significantly reduce the thermal power fluctuating of the heat source and enlarge the high-efficiency working zone. Yu et al [12] designed an ORC system using the concept of double shell-and-tube LTES. This study considered the effects of PCM thermophysical properties and LTES volume on the performance of the proposed ORC system to recover fluctuating thermal energy.…”
Section: Introductionmentioning
confidence: 99%